2006
DOI: 10.1002/srin.200606411
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Surface Defects in Wire Rod Rolling

Abstract: Defects are often present in rolled products, such as wire rod. The market demand for wire rod without any defects has increased. In the final wire rod products, defects originating from steel making, casting, pre‐rolling of billets and during wire rod rolling can appear. In this work, artificial V‐shaped longitudinal surface cracks have been analysed experimentally and by means of FEM. The results indicate that the experiments and FEM calculations show the same tendency except in two cases, where instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…The assumptions were that the welds deform as the surface layer of the base material and that they also deform in the same way as open cracks. The latter assumption can be supported by simulations by Fil- ipovic [12], as described previously. Thus, it is assumed that the evolution of weld and crack depths are similar.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…The assumptions were that the welds deform as the surface layer of the base material and that they also deform in the same way as open cracks. The latter assumption can be supported by simulations by Fil- ipovic [12], as described previously. Thus, it is assumed that the evolution of weld and crack depths are similar.…”
Section: Methodssupporting
confidence: 56%
“…Monid found that changing from box grooves to diamond/square grooves decreased the maximum depth of the decarburized layer with 15-30 % and its depth variation C~el = d i . fA;; I do VA; (2) [12] investigated the evolution of surface defects during wire-rod rolling both experimentally, by rolling short bars with machined longitudinal V-shaped groves positioned at three different sites along the periphery of a round bar, and theoretically by simulating the experimental setup for cracked and for defect-free bars using FEM. When the simulations were compared with experimental work, it was found that the cracks reduced in size faster in experiments than in simulations.…”
Section: Previous Work On Surface Defects and Surface Deformationmentioning
confidence: 99%
“…In heavy rail rolling, continuous casting slab is heated above its temperature of recrystallization and passed through several grooves in the rolling mill (Filipovic et al , 2006). Surface defects such as longitudinal surface cracks or transverse surface cracks of hot rolled steels are potentially serious problems during the rolling process because these might severely affect the quality of the rolled products, and might result in rejection of the rolled materials and mill stoppage (Yu et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2015) investigated the evolution of V-shaped surface transverse cracks with different depths during reversing rolling process of medium plates using 2D FEM. Filipovic et al (2006) studied opening and closing of artificial V-shaped longitudinal surface cracks in wire rod rolling by experiment and MSC MARC software to eliminate the cracks or minimize their negative influence. Yu et al (2009), Yu et al (2008), Yu et al (2006) and Yu and Liu (2009) simulated the behavior of transversal and longitudinal cracks on the slab surface during the vertical–horizontal rolling process by finite element software LS-DYNA, and the influences of the crack size, crack open-angles, the maximum compressive and tensile stress at crack tip, temperature and contact pressure on crack surface, the edger roll shape, the friction coefficient and the fillet radius of grooved edger roll on the closure and growth of cracks were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The market demand for heavy rail without any defects has increased. [2][3][4] Therefore, understanding the metal flow behavior in the process of heavy rail rolling becomes very important. Heavy rail rolling has characteristics of a lot of rolling passes and section grooves, complex cross-sectional shape, large velocity, difference of roll, and concurrence of direct pressure and lateral pressure in groove.…”
Section: Introductionmentioning
confidence: 99%